Streetways : chronicling the homeless in Miami - Provenzo, Eugene F.; Ameen, Edward; Bengochea, Alain; Doorn, Kristen; Pontier, Ryan W.; Sembiante, Sabrina F.; Wilkinson, Lewis (Emerald Publishing Limited : Information Age Pub. Inc., 2014)
StreetWays: Chronicling the Homeless in Miami is a collection of interviews with 28 homeless individuals living in downtown Miami and Miami Beach. Besides extensive photographs of these people and their lives on the street, the book also includes interviews with social service providers, as well as a detailed analysis of homelessness in the United States and more specifically in Miami. The work concludes with a policy analysis and suggestions for addressing issues of homelessness in Miami and the nation.StreetWays attempts to make clear how and why homelessness occurs, and what the actual lives and experiences of the homeless are about. Through extensive interviews and extensive documentary photographs, a selected group of homeless Miamians lose their invisibility as their experiences, needs and aspirations are reported. The book calls for a better understanding of the experience of homelessness places such as Miami, and of the need to understand homelessness as an issue of diversity and human rights.